Large-scale synthesis of CuS hexaplates in mixed solvents using a solvothermal method - Thongtem T. (2014)
Large-scale covellite CuS hexaplates were successfully synthesized by the 200 °C solvothermal reactions of CuCl2.2H2O and (NH4)2S in C2H5OH-H2O mixed solvents containing HCOOH as a pH stabilizer, including different amounts and molecular weights (MWs) of polyethylene glycol (PEG). By using XRD and SAED, CuS (hcp) was detected. XRD peaks of the product, synthesized in a solution containing 5 g PEG6000 and 1.5 ml HCOOH for 5 h, are in accordance with those of the simulation and database. The (110) peak shows the preferential growth, corresponding to the hexaplates, characterized using SEM, TEM and HRTEM. CuS hexaplates with the (100) and (010) lattice planes at an angle of 120° were detected on the flat surface, and the (002) lattice plane on the edge. UV-vis absorption edge was detected at 610 nm (2.03 eV), and the PL emission at 361 nm (3.43 eV). Phase and morphology formations were also explained according to the experimental results. © 2009 Elsevier B.V. All rights reserved.